Ectopic Overexpression of Porcine Myh1 Increased in Slow Muscle Fibers and Enhanced Endurance Exercise in Transgenic Mice - Jin Seop Ahn (International Journal of Molecular Sciences, 2018)
Myosin heavy chain (MyHC) isoforms consist of Myh7, Myh2, Myh1, and Myh4, which are expressed in skeletal muscle tissues during postnatal development. These genes influence the contraction–relaxation activity in skeletal muscles and are involved in determining muscle composition such as the proportion of fast-to-slow and/or slow-to-fast fiber types. Among them, Myh1 is associated with skeletal muscle contraction and is involved in both slow-to-fast and fast-to-slow transition. However, the muscle transition mechanism is not well understood. For this study, we first produced porcine Myh1 transgenic (TG) mice to study whether the ectopic expressed porcine Myh1 gene had any effects on muscle composition, especially on slow-type muscle components. Our results showed that the factors associated with slow muscles, such as Myh7, Myoglobin, Troponin (slow-type units), and cytochrome C, were highly expressed in the quadriceps muscles of Myh1 transgenic mice. Furthermore, the ectopic porcine MYH1 protein was located only in the slow-type muscle fibers of the quadriceps muscles in Myh1 transgenic mice. In physical endurance tests, Myh1 transgenic mice ran longer and further on a treadmill than wild-type (WT) mice. These data fully supported our hypothesis that Myh1 is associated with slow muscle composition, with overexpression of Myh1 in muscle tissues possibly being a new key in modulating muscle fiber types. Our study provides a better understanding of muscle composition metabolism, physical mobility, and genetic factors in muscle fatigue.